PRESENT SCENARIO OF DIGITAL SERVICE IN INDIA - Raji, Dr. S.Ezhil (International Journal of Psychosocial Rehabilitation, 2020)
The present paper shows the understandings of certain aspects respect of present scenario of digital service in India such as: digital services, digital India, digital services applications in India (Government), present scenario of digital service providers in India, and previous reports in digital services. Researcher revealed the previous reports of the Cognizant, Ministry of Electronics and Information Technology, PwCPL, NASSCOM, and PTI. The present paper portrait that the digital services in India is the growth of the significant level, but it shows the middle level of growth. It will have the chance of growth better in the future (as per the law of economics if everything remains constant). Indian central and state governments should be focused to develop the economy of the nation and giving importance to all the sectors of the economy. The BSNL has its market share in 2011-12 54.97 per cent but now what happen, the imperfect decision making will reduce the public sector organization because of giving opportunities to private like R-Jio. Now the government has announced to some subsidies to the private telecom industries. These are totally willing give abrupt and adverse effect on the economy.